Promoting and impeding safety – A qualitative study into direct and indirect safety leadership practices of constructions site managers. (April 2019) - Grill, Martin; Nielsen, Kent
Highlights: The leadership of construction site managers is important for occupational safety. Site managers influence safety through direct and indirect leadership behaviors. Positive leadership is to plan, coordinate, role model, monitor and proactively amend. Negative safety leadership can emerge from avoiding unpopular leadership behavior. Abstract: Managerial leadership is an essential element in preventing occupational risk and increasing safety performance. The aim of the present study was to investigate construction site managers' experiences of how their leadership practices influence safety performance at construction sites in order to expand present knowledge on the influence of leadership on occupational safety. The critical incident technique was applied in interviews with 37 construction site managers. The results provide detailed descriptions of how construction site managers both promote and impede construction site safety performance through their leadership behaviour. The core leadership behaviours involved in positively influencing safety were found to be continuous planning and coordination, role modelling, monitoring work and proactively correcting deviations. Negative safety leadership was found to emerge when site managers were subjected to positive feedback to meet deadlines, minimise costs and refrain from unpopular leadership behaviour. Positive safety leadership may therefore be encouraged by minimizing such feedback and/or providing site managers with positive feedback for engaging in planning, coordinating, role modelling, and monitoring. It may also be encouraged by training and coaching site managers to acknowledge their leadership responsibilities, to communicate clear expectations, to execute individual and collective risk-assessment, and to execute proactive monitoring and feedback procedures.